The Effect of Endotoxin-Induced Inflammation on the Activity of the Somatotropic Axis in Sheep - Maciej Wójcik; Dorota Anna Zieba; Joanna Bochenek; Agata Krawczyńska; Marcin Barszcz; Alina Gajewska; Hanna Antushevich; Andrzej Przemysław Herman (International Journal of Inflammation)
The hypothalamic-pituitary-somatotropic (HPS) axis controls many physiological and pathophysiological processes. The phenomenon of insensitivity to growth hormone resistance (GHres) was previously reported to be due to the development of inflammation. Therefore, the primary aim of the study was to determine the impact of inflammation caused by lipopolysaccharides (LPS) on the secretory activity of the HPS axis in sheep. The further goal was to determine the effect of inflammatory factors on individual components involved in intracellular signal transduction to GH via the GH receptor (GHR). The research was carried out on 24 seasonal sheep kept under a short-day photoperiod, randomly divided into two groups. Before the experiment, the sheep estrous cycles were synchronized. The results of the current study in a sheep model showed that inflammation impairs the activity of the somatotropic axis. On the one hand, LPS injection stimulated (p<0.01) GH secretion, and on the other hand, it reduced the liver’s sensitivity to this hormone by directly reducing (p<0.01) GHR expression and activating the GHR inhibitory signal transduction mechanism. A symptom of such an inhibitory postreceptor signaling pathway may be due to an increase in SOCS3 expression (p<0.01). The effect of various inhibition pathways is a significant reduction in the expression of the main transcription activator IGF1-STAT5B (p<0.05). The action of GHres in the liver resulted in the inhibition of IGF1 secretion, which in the long term may have negative consequences for growth and development. Our study suggests that disruption of the GH cell signaling pathway may be one of the important elements of the pathophysiology of inflammation. It can suppress growth and hepatic metabolism to spare energy expenditure.